Link and Node Removal in Real Social Networks: A Review - Bellingeri, Michele; Bevacqua, Daniele; Scotognella, Francesco; Alfieri, Roberto; Nguyen, Quang; Montepietra, Daniele; Cassi, Davide (Frontiers in Physics, 2020)
In this mini-review we discuss the problem of links/nodes removal in real social networks. We resume findings from works that adopted the two most common measure of network robustness, i.e. the largest connected component (LCC) and the network efficiency (Eff). We consider both binary-topological and weighted network approaches by elucidating how links/nodes removal affect the spreading of information in real social networks. We show that to investigate the response of social network subjected to links/nodes removal can be useful to manage many important practical problems. This mini-review outlines that to perform more real and precise prediction of social networks response to links/nodes removal it is necessary to account the heterogeneity in link weights. Eventually, we propose promising lines for future researches in social network science.